Pelaksanaan Sistem Zonasi Pada Penerimaan Peserta Didik Baru - Kris Setyaningsih; Ibrahim Ibrahim; Uswatun Hasanah (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2023)
This article is entitled the implementation of the zoning system in accepting new students at SMAN 3 Lais. The problem in this article was about how to implement the zoning system for accepting new students at SMA Negeri 3 Lais. The type of research was used descriptive-qualitative and conducted directly in the field. The data for this study were collected through observation, interview, and documentation. The data analysis techniques in this study are data collection, data reduction, data presentation, and data verification. The results of this study indicate the implementation of the zoning system in accepting new students at SMA Negeri 3 Lais has gone well, such as providing motivation by giving rewards to teachers, conducting guidance and direction, and establishing good coordination and communication.